1998
DOI: 10.1001/jama.280.18.1590
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Amitriptyline for Pain Due to HIV-Related Peripheral Neuropathy<SUBTITLE>A Randomized Controlled Trial</SUBTITLE>

Abstract: Context.-Peripheral neuropathy is common in persons infected with the human immunodeficiency virus (HIV) but few data on symptomatic treatment are available.Objective.-To evaluate the efficacy of a standardized acupuncture regimen (SAR) and amitriptyline hydrochloride for the relief of pain due to HIV-related peripheral neuropathy in HIV-infected patients.Design.-Randomized, placebo-controlled, multicenter clinical trial. Each site enrolled patients into 1 of the following 3 options: (1) a modified double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(143 citation statements)
references
References 31 publications
2
133
1
3
Order By: Relevance
“…The results indicated a small decline in pain scores at 6 and 14 weeks for both groups, with no significant difference between real and sham acupuncture. The results from the present study are markedly different from Shlay et al's (1998) findings in that we observed significant reductions in pain levels after 5 weeks of acupuncture. The greater decrease for pain scores in the present study could be due to the specificity of the acupuncture treatment for particular symptoms reported by the participants.…”
Section: Acupuncture Pain and Peripheral Neuropathy 453contrasting
confidence: 99%
See 2 more Smart Citations
“…The results indicated a small decline in pain scores at 6 and 14 weeks for both groups, with no significant difference between real and sham acupuncture. The results from the present study are markedly different from Shlay et al's (1998) findings in that we observed significant reductions in pain levels after 5 weeks of acupuncture. The greater decrease for pain scores in the present study could be due to the specificity of the acupuncture treatment for particular symptoms reported by the participants.…”
Section: Acupuncture Pain and Peripheral Neuropathy 453contrasting
confidence: 99%
“…A relatively large clinical trial (Shlay et al, 1998) examined the effects of a standardized regimen of acupuncture on pain related to peripheral neuropathy in HIV-infected subjects compared to a sham control group. The results indicated a small decline in pain scores at 6 and 14 weeks for both groups, with no significant difference between real and sham acupuncture.…”
Section: Acupuncture Pain and Peripheral Neuropathy 453mentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no evidence that amitriptyline is more effective than placebo for painful HIV-SN, [11][12][13] its proven efficacy in other types of neuropathic pain [22] prompted an expert panel to recommend it as a first-line option for HIV-SN pain in SA. [7] These patients were therefore receiving a recommended treatment, albeit at a relatively low dose (25 -50 mg/d).…”
Section: Discussionmentioning
confidence: 99%
“…[4] Several national and international agencies [5][6][7][8][9][10] have recommended the tricyclic antidepressant amitriptyline for HIV-SN pain, despite evidence that this is no better than placebo. [11,13] Despite the high prevalence [1,2] and considerable impact of HIV-SN, and the lack of proven effective analgesics, few data exist describing the frequency, type and dosage of pain medication patients are receiving. We are aware of only one retrospective case review, with low-quality case ascertainment criteria, that attempted to describe the treatment of HIV-SN pain in a clinical setting.…”
mentioning
confidence: 99%